Software Design For Production Planning Of Chrysantemum Fresh Flower (Case Study At Pt. Alam Indah Bunga Nusantara, Cipanas – West Java) - Ratna Sari; Kudang Boro Seminar (Jurnal Teknologi Industri Pertanian, 2009)
This paper describes the development and implementation of software production planning of chrysantemum fresh flower. The software utilizes quantitative method time series (moving average and exponential smoothing) for predicting the demand of fresh flowers. The software is also equipped with a simulation utility (using Monte Carlo method) for computing total cost activity in one greenhouse tunnel during one period plant. Based on the case test observation carried out at PT. Alam Indah Bunga Nusantara Cipanas, it is obtained that the error introduced by qualitative forecasting is 15.12%. The errors of quantitative forecasting using moving average and exponential smoothing are 8.32 %, and 18.72 % respectively. The mean value of total cost simulation (Rp 28.291/m2) does not differ significantly from while the mean value of the real cost production (Rp 28.554/m2). This introduces error equal to 0.92%. Keywords: Chrysantemum, Monte Carlo, planning, production, simulation